Efforts to reduce the number of job seekers through entrepreneurship workshops and training on the production of tilapia fish crackers - Sri Yaumi; Ika Purwanti; Mesra Berlyn Hakim; Norma Anggraini Rahmawati; Jihan Finaya; Fiki Fahrur Nizam; Putri Ayu Nor Anggraini; Abdul Majid (Universitas Muhammadiyah Magelang, 2024)
The majority of Ngujungrejo residents earn their livelihoods through farming, primarily producing rice and various types of fish. They typically sell the fish fresh at nearby markets. However, they encounter challenges during periods of abundant harvests, as oversupply leads to price drops and the risk of fish spoilage, especially tilapia. Additionally, there has been a rise in the number of job seekers over the past three years. The goal of this initiative is to enhance residents' entrepreneurial skills and understanding while improving their ability to process harvests into higher-value products. Methods employed include surveys, entrepreneurship workshops, training sessions on producing tilapia fish crackers, and evaluation. The outcome of this effort has been a 60% increase in knowledge and understanding of entrepreneurship and a 75% improvement in skills related to tilapia fish production. This growth is anticipated to empower participants to establish home-based industries, consequently reducing the number of job seekers in the area.